2005
DOI: 10.1007/s10529-004-7884-3
|View full text |Cite
|
Sign up to set email alerts
|

Mediated electrochemical measurement of the inhibitory effects of furfural and acetic acid on Saccharomyces cerevisiae and Candida shehatae

Abstract: The toxic effects of furfural and acetic acid on two yeasts, Saccharomyces cerevisiae and Candida shehatae, were evaluated using an electrochemical method. Intracellular redox activities were lowered by 40% and 78% for S. cerevisiae and C. shehatae, respectively, by 8 g furfural l(-1), and by 46% and 67%, respectively, by 8 g acetic acid l(-1). The proposed method can accurately measure the effects of inhibitors on cell cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Thomsen reported furfural concentration ranging from 0.03 to 1.2 g/L during hydrothermal treatment of wheat straw (Thomsen et al, 2009). The relative cellular redox activity of Candida shehatae, a xylose fermenting yeast strain, was reduced to 65% when furfural concentration was above 2 g/L and 55% when acetic acid concentration was 4 g/L (Zhao et al, 2005). Beside their inhibition capability on fermentation, furfural and acetic acid hold valuable promise for the development of a biorefinery that includes the process of HWE.…”
Section: Mass Removed By Hot Water Extraction (Hwe) and Composition Omentioning
confidence: 99%
“…Thomsen reported furfural concentration ranging from 0.03 to 1.2 g/L during hydrothermal treatment of wheat straw (Thomsen et al, 2009). The relative cellular redox activity of Candida shehatae, a xylose fermenting yeast strain, was reduced to 65% when furfural concentration was above 2 g/L and 55% when acetic acid concentration was 4 g/L (Zhao et al, 2005). Beside their inhibition capability on fermentation, furfural and acetic acid hold valuable promise for the development of a biorefinery that includes the process of HWE.…”
Section: Mass Removed By Hot Water Extraction (Hwe) and Composition Omentioning
confidence: 99%
“…This suggests some delay in "switching on" glucose assimilation by Saccharomyces cerevisiae and Wickerhamomyces anomalus. The "spiked mode" of glucose currents was not detected during the former investigation of yeast redox activities [2][3][4][5][6][7][8][9][10][11][12] since the experimental conditions were different. Non-wild type Saccharomyces cerevisiae strains were pre-incubated with glucose before measurements; therefore, the "spiked mode" of responses to glucose was not observed.As determined previously [17][18][19], the investigated wild type yeast strains varied in rates of glucose assimilation and ethanol production, biocide and biostatic properties, and in abilities to secrete killer toxins, pigments and other yet not identified substances.…”
Section: Discussionmentioning
confidence: 99%
“…Electrochemistry provides the possibility of monitoring redox processes related to the metabolic activity of living cells [2][3][4][5][6][7][8][9][10][11][12]. Direct electron transfer between the electrode and the redox centers of the enzymes in the cells is, as a rule, not achievable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research of redox processes occurring in the intact yeast cells [18][19][20][21] revealed that amperometric measurements using only negatively charged ions (such as ferricyanide) were not possible probably due to electrostatic interaction of mediator with phosphate moieties of membrane phospholipids. The double mediator system containing both lipophilic (such as menadione) and hydrophilic (ferricyanide) was needed to monitor the redox activity inside the yeast cell.…”
Section: Introductionmentioning
confidence: 99%